1996
DOI: 10.1111/j.1432-1033.1996.00468.x
|View full text |Cite
|
Sign up to set email alerts
|

The Escherichia Coli‐Derived Fab Fragment of the IgM/κ Antibody IN‐1 Recognizes and Neutralizes Myelin‐Associated Inhibitors of Neurite Growth

Abstract: A recombinant Fab fragment was prepared from the monoclonal I g M k antibody IN-1, which neutralizes central nervous system myelin-associated neurite growth inhibitors both in vitro and in vivo. The variable domain gene sequences were amplified and cloned after cDNA synthesis from the hybridoma RNA. After insertion into the tet promoter vector pASK85, which provided the constant domains of class IgGl/K, equipped with a Hish tag, large amounts of the Fab fragment were produced in Escherichiu coli by medium cell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
43
0

Year Published

1997
1997
2007
2007

Publication Types

Select...
9

Relationship

6
3

Authors

Journals

citations
Cited by 32 publications
(45 citation statements)
references
References 36 publications
2
43
0
Order By: Relevance
“…5) bNI-220 is present in spinal cord myelin, in line with the previous finding that mAb IN-1 immunostains CNS myelin (32). 6) Immunoprecipitation of bovine CNS myelin by mAb IN-1 or an IN-1 Fab depleted about two thirds of the inhibitory activity and precipitated a high molecular mass complex comprising several bands including a prominent band at 220 kDa (25,31). 7) Analytical analysis of the active gel-eluted 220 kDa band by two-dimensional PAGE revealed one major spot, indicating that bNI-220 was purified to homogeneity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…5) bNI-220 is present in spinal cord myelin, in line with the previous finding that mAb IN-1 immunostains CNS myelin (32). 6) Immunoprecipitation of bovine CNS myelin by mAb IN-1 or an IN-1 Fab depleted about two thirds of the inhibitory activity and precipitated a high molecular mass complex comprising several bands including a prominent band at 220 kDa (25,31). 7) Analytical analysis of the active gel-eluted 220 kDa band by two-dimensional PAGE revealed one major spot, indicating that bNI-220 was purified to homogeneity.…”
Section: Discussionmentioning
confidence: 99%
“…A monoclonal antibody (mAb IN-1), which has been raised against rat , neutralizes the neurite growth inhibitory property of differentiated oligodendrocytes and [24][25][26][27][28][29][30]. Immunoprecipitation of CNS myelin proteins by the mAb IN-1 removed more than 50% of inhibitory substrate properties (25,31). Immunohistochemistry revealed that mAb IN-1 stains white matter and myelin in the whole brain and spinal cord from adult rats (32).…”
mentioning
confidence: 99%
“…Recently, it became possible to clone the DNA sequences coding for antibody chains and to express tailor-made recombinant antibodies in large quantities in bacteria (Skerra and Plückthun, 1988;Orlandi et al, 1989). We have cloned the cDNAs for the variable regions of the Fab light and heavy chain, including the antigen binding site of mAb IN-1, and expressed a monovalent, recombinant fragment, rIN-1 Fab (ϳ45 kDa molecular mass), that was able to neutralize Nogo-A in vitro (Bandtlow et al, 1996). rIN-1 Fab can be produced in large quantities, concentrated, stored, and infused as a pure reagent to the CNS in a way potentially also applicable to human patients.…”
Section: Abstract: Cns Regeneration; Nogo-a; Spinal Cord Injury; Axomentioning
confidence: 99%
“…Selenomethionine (SeMet)-labeled protein was produced in the methionine-auxotrophic E. coli strain B834(DE3) and grown in minimal medium with SeMet (0.3 mM) substituted for methionine. The cDNA of the variable domains of the mouse monoclonal antibody 8-18C5 was subcloned into the expression vector pASK107, yielding the chimeric (8-18C5)-Fab composed of the 8-18C5 variable domains, the human IgG constant domains, and the Strep tag II fused to the C terminus of the heavy chain (9,10). (8-18C5)-Fab was produced by periplasmic secretion in E. coli and purified by streptavidin affinity chromatography and gel filtration (11).…”
Section: Preparation Of Recombinant Mog Igd and The Mog Igd -(8-18c5)mentioning
confidence: 99%